(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2020)
The health care provided by health institutions and all kinds suffers from many problems, and since the health services provided are related to human life, it is necessary to shed light on this activity and identify the causes of these problems. This research aims to Definition of health institutions (hospitals) Performance audit of these institutions according to the latest indicators, which are the standards of health accreditation for hospitals, specifically the basic standards issued by the Health Care Accreditation Council (HCAC) to reach the level of performance and Knowledge of Constraints that lead to in an acceptable manner consistent with the approved standards. In theoretical and practical study, a number of conclusions were reached 1- Don’t use of health accreditation standards of hospitals (HCAC) as indicators to develop the level of health performance of hospitals. 2- The level of health performance in health institutions, have not upgrade because lack of policies and procedures by working owners precisely, mainly relying on legacy work contexts. The most important recommendations reached were: 1- Accreditation of the Health Care Accreditation standards for hospitals, in the development of the health performance of the institutions and focus on them in the performance audit indicators of both the Ministry of Health and the Federal Board of supreme Audit. 2- A Commitment of policies and procedures by the staff very accurately, and not adopt the legacy work contexts because this institutions related to the patient’s life.